Aerial identification and quantification of nesting sites of Golden Eagle (Aquila chrysaetos) in the mountain ranges of central Baja California Peninsula, Mexico - Gonzalo De León-Girón; Diego Toscano; Gorgonio Ruiz-Campos; Catalina Porras-Peña; Fernando Escoto-Rodríguez; Víctor Gelasio Sánchez-Sotomayor; Celerino Montes-García; Juan Vargas-Velazco; Ismael Cruz-Molina; Robert N. Fisher (Revista Mexicana de Biodiversidad)
Aerial census for identification and quantification of nesting sites of Golden Eagle was performed through the mountain ranges of the central Baja California Peninsula, Mexico from 5 to 8 April 2021. We identified a total of 113 nests and 12 territories of Golden Eagle on a sampling trajectory of 1,203 km that encompassed a surface of 176,000 ha. The highest abundance of nests (n = 57) was recorded between 29º and 30º N latitudes with elevations ranging between 600 and 700 m (n = 35) in the Valle de Los Cirios Protected Natural Area, which is mainly associated with mountain biotopes with steep cliffs and ample alluvial valleys that promote foraging and nesting sites for this species. The number of nests of Golden Eagle showed an inverse relationship with the altitude along a latitudinal gradient. This study reports new nesting sites of Golden Eagle in the central peninsular region that includes the mountain ranges of Matomí, Jaraguay, and La Libertad.